Tsunaiyyah al-Lughah wa izdiwaj al-Lisan fi al-Lughah al-'Arabiyyah - Ii Rahmanudin, ((الطموحات ) EL-THUMUHAT, 2023)
This study will examine bilingualism, the difficulty of Arabic bilingualism, and how these issues arise when classical and informal languages are used by different people in different nations and civilizations. The researcher expanded the problem of bilingualism as a result of the substitutions and linguistic variations that existed between them. In descriptive investigations, scientists adopt a qualitative methodology. According to the findings of this study, bilingualism between classical and colloquial languages is a significant issue because the distinction between cultural, intellectual, social, economic, educational, political, and national life is made by the deviation of classical language and its replacement in everyday language. Because both are virtues, kindly make the Central Arabian people.